The Role of Duration in Multinational Investment Strategies - Mudambi, Ram (Journal of International Business Studies, 1998)
The location of investment by multinational enterprises has been investigated from many perspectives. It has been suggested that investment may be motivated by experience of a particular location represented by tenure of operations. In contrast, portfolio considerations suggest that increased investment in a given location increases risk exposure. In this paper, the question of whether a multinational with a longer duration of operations at a particular location is more likely to invest further is addressed after taking portfolio risk into account. A conceptual model of multinational investment strategy is developed and empirically tested using data from a survey of multinational enterprises operating in the West Midlands region of the United Kingdom. Two innovative non-parametric tests for duration dependence are applied. After normalising for portfolio considerations, it is found that multinational investment is significantly duration dependent, i.e., firms with a longer tenure of operations are significantly more likely to invest in any given period. This finding has important implications for the strategy of inward investment agencies. In particular, an investment agency is short-sighted if it seeks to attract new investors if that is at the expense of neglecting multinationals with current operations in its jurisdiction.